Comparison of Two Luting Agents Used for the Retention of Cast Dowel and Cores - Barry Habib, DMD, MS;1 Joseph Anthony von Fraunhofer, PhD;2 (Journal of Prosthodontics, 2005)
The first purpose of this study was to compare the retentive values of zinc phosphate and Panavia F resin cements when used for luting cast dowel and cores